2007
DOI: 10.1002/ijc.23186
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancers overexpress the antimicrobial protein hCAP‐18 and its derivative LL‐37 increases ovarian cancer cell proliferation and invasion

Abstract: The role of the pro-inflammatory peptide, LL-37, and its proform, human cationic antimicrobial protein 18 (hCAP-18), in cancer development and progression is poorly understood. In damaged and inflamed tissue, LL-37 functions as a chemoattractant, mitogen and pro-angiogenic factor suggesting that the peptide may potentiate tumor progression. The aim of this study was to characterize the distribution of hCAP-18/LL-37 in normal and cancerous ovarian tissue and to examine the effects of LL-37 on ovarian cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
123
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 45 publications
6
123
3
1
Order By: Relevance
“…In vitro studies revealed that ovarian cancer cells treated with LL-37 are activated to proliferate at a rate similar to that for other mitogens, such as epidermal growth factor. 18 Similarly, higher proliferation was observed in breast cancer cells overexpressing LL-37. 19 The mitogenic effects of LL-37 on lung cancer cells and lung cancer xenografts are accompanied by phosphorylation of the epidermal growth factor receptor and subsequent activation of the Ras/mitogen-activated protein kinase cascade.…”
mentioning
confidence: 77%
“…In vitro studies revealed that ovarian cancer cells treated with LL-37 are activated to proliferate at a rate similar to that for other mitogens, such as epidermal growth factor. 18 Similarly, higher proliferation was observed in breast cancer cells overexpressing LL-37. 19 The mitogenic effects of LL-37 on lung cancer cells and lung cancer xenografts are accompanied by phosphorylation of the epidermal growth factor receptor and subsequent activation of the Ras/mitogen-activated protein kinase cascade.…”
mentioning
confidence: 77%
“…MSC-conditioned medium was analyzed by a luminex-based assay. Zymography assays were performed as before (1). Quantification of band intensity was performed using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…istological examination of ovarian, breast, and lung tumors has shown that the pro-inf lammatory peptide LL-37 (leucine, leucine-37) is up-regulated in these malignancies (1)(2)(3). LL-37 was originally identified as a component of host defense peptides released by innate immune cells to combat microorganisms (4)(5)(6).…”
mentioning
confidence: 99%
“…Human cationic antimicrobial protein 18 (hCAP-18) is the only known member of the cathelicidin family in humans. The active peptide LL-37 is overexpressed in breast, lung, and ovarian tumors, probably functioning as an autocrine survival factor (91)(92)(93). It may also promote tumor growth through angiogenesis and recruitment of CD45 + cells (69).…”
Section: Cancermentioning
confidence: 99%